IMPLEMENTASI KURIKULUM MERDEKA BELAJAR TERHADAP MATA PELAJARAN PAI DALAM MENINGKATKAN RELIGIUSITAS PESERTA DIDIK DI SMKN 8 GARUT - Luthfi MR, Rifyal; Sopyan (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
This research is based on the concept of “Independent Learning” introduced by the Minister of Education and Culture of the Republic of Indonesia Nadiem Makarim in his remarks at the 2019 National Teachers' Day (HGN) ceremony. This idea emerged as a reaction to the demands of the education system in the Industrial Revolution 4.0 era. The purpose of this study is to determine (1) the implementation of the Independent Learning Curriculum on Islamic Religious Education Subjects at SMKN 8 Garut, (2) the implementation of the Independent Learning Curriculum on Islamic Religious Education subjects in increasing student religiosity at SMKN 8 Garut. The Independent Curriculum is present as an effort to renew the national education system that emphasizes more on student-centered learning, learning differentiation, and character building, including religious values. This study uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with the principal, vice principal for curriculum, Islamic Religious Education teachers and students, as well as the exploration of documentation of the Education Unit Curriculum (KSP) and learning activities. The data sources used are primary and secondary data sources. The data analysis procedure used is descriptive analysis, namely data reduction, data presentation and drawing conclusions. The results of the study show that the implementation of the Independent Curriculum in Islamic Religious Education learning at SMKN 8 Garut is carried out through intracurricular activities in the learning process as well as through co-curricular activities in the Pancasila Student Profile Strengthening Project, a contextual approach, and integration of spiritual values in intracurricular and extracurricular activities. The results show that (1) The implementation of the Independent Learning Curriculum at SMKN 8 Garut has been running well but still needs development and improvement, (2) The implementation of the Independent Learning Curriculum in Islamic Religious Education subjects has been carried out in accordance with the procedures in the Implementation of the Independent Learning Curriculum but in the technical learning it still pays attention to the needs of students according to the demands of their environment, (3) Islamic Religious Education learning has been able to increase the religiosity of students at SMKN 8 Garut, as evidenced by the increasing spiritual attitudes and strengthening of students' characters both in the educational unit environment and in the community. At the technical level, the Implementation of the Independent Learning Curriculum still has several obstacles both in terms of facilities and infrastructure, mindsets and responses from educators and students, especially the lack of structured assistance in its implementation.